2018
DOI: 10.3198/jpr2017.09.0063crgs
|View full text |Cite
|
Sign up to set email alerts
|

Registration of BTx623ms8, a New and Easily Identifiable Nuclear Male Sterile Mutant in Sorghum

Abstract: The USDA–ARS has released a new nuclear male sterile sorghum [Sorghum bicolor (L.) Moench] mutant BTx623ms8 (Reg. No. GS‐786, PI 682727). Previously, seven sorghum nuclear male sterile mutants have been reported, but three are no longer available. Here we register a new nuclear male sterile mutant isolated from a mutagenized BTx623 mutant library that is genetically different from any of the four male sterile mutants currently available. The ms8 mutant had microscopic transparent anthers that abort early durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The dw5 mutant was backcrossed to the male sterile NIL of BTx623, BTx623 ms8 (Xin et al, 2018) and the backcrossed F 1 and F 2 populations were used to examine the genetic control of dwarf phenotype in dw5 mutant. The results of plant height segregation are provided in Table 1, and the plant height measurement data are provided in Table 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dw5 mutant was backcrossed to the male sterile NIL of BTx623, BTx623 ms8 (Xin et al, 2018) and the backcrossed F 1 and F 2 populations were used to examine the genetic control of dwarf phenotype in dw5 mutant. The results of plant height segregation are provided in Table 1, and the plant height measurement data are provided in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…he dwarf phenotype of the mutant plants was conirmed in M 5 progenies and F 2 segregation population under ield condition at the USDA-ARS Cropping Systems Research Laboratory in Lubbock, TX (33.58° N, 101.85° W, elevation 976 m). In 2017, the seed of original wild-type BTx623, the male sterile near-isogenic line (NIL) of BTx623 (BTx623 ms8 ) (Xin et al, 2018) used as female for backcrossing, the dw5, and backcrossed F 1s were planted in the winter nursery ield in Guayanilla, Puerto Rico (18.0373° N, 66.7963° W, elevation 49 m), on 11 Dec. 2017. he plot size for all plantings at both Lubbock and Puerto Rico locations was 4.6 m long with 1.02 m row spacing. About 60 sorghum seeds per row were planted per plot, and the planting depth was about 3 cm.…”
Section: Methodsmentioning
confidence: 99%
“…Pollen from the bagged bmr mutants was crossed to BTx623ms8, a near-isogenic line of BTx623 with a nuclear male sterile mutation (Xin et al, 2017(Xin et al, , 2018. Due to the large number of the mutants selected at the M 2 generation that displayed poor seed setting, systematic evaluation of mutant phenotypes was deferred to the M 3 generation.…”
Section: Parental Background and Germplasm Developmentmentioning
confidence: 99%
“…We then performed complementation analyses to determine whether ms9 is allelic to any previously reported sorghum NMS mutants (Pedersen and Toy, 2001;Xin et al, 2018). Phenotyping results revealed that all cpF1 plants from the complementation crosses between male-sterile plants of known NMS lines and heterozygous BC2F1 ms9 plants were fertile (Table 1).…”
Section: Ms9 Is a Novel Recessive Nuclear Male Sterility Mutantmentioning
confidence: 99%